Diagnosis and treatment of outpatient insomnia by psychiatric and nonpsychiatric physicians - Shorr, R I; Bauwens, S F (The American journal of medicine, 1992)
Insomnia is commonly encountered in general medical practice, but little is known about how primary care physicians manage this problem. We reviewed medical records describing 536 patient encounters in which either triazolam (Halcion) or flurazepam (Dalmane) was prescribed for outpatient use. Only 12% of the progress notes written by internists or surgeons contained even a remote reference to sleep, whereas 74% of psychiatrist's notes contained at least some sleep symptom documentation. In a multivariate analysis including the number of medical and psychiatric diagnoses, patient age, and physician gender, only the prescriber department was independently associated with the presence of symptom documentation. We also found that 30% of the prescriptions written by internists or surgeons were for inappropriately large quantities of these drugs (180 or more doses) compared with 6% of the prescriptions written by psychiatrists. We conclude that the evaluation of insomnia by nonpsychiatrists is often incomplete and that hypnotic drugs may be inappropriately prescribed by these physicians. Further efforts are needed to improve the management of insomnia by primary care physicians in the outpatient setting.